Agarwood Market Report - Puteri Fadzline, Tamyez; Cheng, Jack Kie; Fazeeda, Mohamad; Saiful Nizam, Tajuddin; Ridzuan, Darun (2018)
Agarwood is known as the most expensive wood in the world with its high value of culture and religion, as well as its wide usage in medicine, and fragrance and cosmetics. Currently, agarwood products specifically agarwood oil or oud can only be obtained from three sources, from the dwindling supply of the natural forests, sustainable plantation, and adulteration. The top ten export destinations are United Arab Emirates, Singapore, Malaysia, India, Laos, Japan, China, Taiwan, Oman, and Hong Kong. The global agarwood market is currently estimated at a minimum of USD $6 billion dollars (Selina Akter, Md Tavir Islam, Mohd Zulkefeli, 2013), and can reach to 12 billion of market value (Capital, 2016a; Chetpattananondh, 2012). The fragrance market in the Middle East and North Africa as among the biggest market is predicted to increase to a value of 6 billion USD in 2018 (25.9%), and 2 billion USD (40.4%) in Saudi Arabia (Euromoniter, 2016). The global agarwood essential oil market is estimated to grow at the Compound Annual Growth Rate (CAGR) of 4.2% during 2016-2022 (Store, 2017). There is no clear grading and pricing standard for agarwood and agarwood products in the global consumer market. The traders fully rely on any of the eight grading techniques applied by the industry players. Supply rates are only 40% of the demand and a litre of Agarwood oil can be sold for around $US10, 000 - 14,000 on the market (Colombogazette, 2016; Institute, 2007). The main leaders for cultivated agarwood are Ajmal India, Treedom Thailand, and Asia Plantation Capital. These companies require a time consuming planning and rigorous effort through professional management and long-term planning over a 7-year period. Synthetic agarwood producers are Firmenich and Givaudan. The volume sold per year is 4,870 litres in 2012 which is mainly used for perfume and cosmetics (Euromoniter, 2016). One company that is closely competing with Evolva is Efflorus, a company from Canada. They claim to launch their ‘bio-oud’ in the market by 2017 (Synbiowatch, 2016). There is likely a competition for biosynthesized agarwood after considering several important factors. Biosynthetic production of agarwood is the only sustainable way to keep agarwood alive. Agarwood has a long history in Malaysia along with more than 18 countries of trading worth millions of US dollars every year (MTIB, 2017). Nonetheless, there are a number of factors that inhibits the growth of this industry where in fact, Malaysia is one of the main producers of agarwood in the world. Thus, this study explores the position of Malaysia in the global agarwood industry while identifying the issues pertaining the industry. This study also suggests a few recommendations to ensure a sustainability agarwood industry in Malaysia.